Increased vaginal pH in Ugandan women: What does it indicate? - Donders, G. G.G.; Gonzaga, A.; Marconi, C. [UNESP]; Donders, F.; Michiels, T.; Eggermont, N.; Bellen, G.; Lule, J.; Byamughisa, J. (Springer Nature, 2016)
Abnormal vaginal flora (AVF),indicative of bacterial vaginosis (BV) and/or aerobic vaginitis (AV),amongst other abnormalities,is a risk factor for multiple complications in pregnant as well as non-pregnant women. Screening for such conditions could help prevent these complications. Can self-testing for increased vaginal pH reliably detect BV and other high-riskmicroflora types,and is this more accurate than performing Gram stain-based Nugent score when screening for high-risk microflora? A total of 344 women presenting at different outpatient clinics in Mulago Hospital and Mbuikwe Outpatient clinics in Kampala,Uganda,were asked to test themselves by introducing a gloved finger into the vagina and smearing it on a microscopy slide,on which a pH strip was attached. Self-assessed categories of normal (pH 3.6-4.4),intermediate (4.5-4.7) or high pH (>4.7) were compared with demographic and with centralised microscopic data,both in air-dried rehydrated wet mounts (Femicare),as well as in Gram-stained specimens (Nugent). AVF was present in 38 %,BV in 25 % and AV in 11 % of patients. High pH and AVF is correlated with human immunodeficiency virus (HIV),infertility,frequent sex,but not vaginal douching. Screening for raised pH detects 90 % of AVF cases,but would require testing over half of the population. As AV and non-infectious conditions are frequent in women with AVF and high pH,Nugent score alone is an insufficient technique to screen women for a high-risk vaginal microflora,especially in infertile and HIV-infected women.